2017
DOI: 10.1530/rep-17-0061
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular responses of adult testis to changes in nutrition: novel insights from the sheep model

Abstract: This review explores the cellular and molecular mechanisms that regulate spermatogenesis in the post-pubertal testis that is regressing in response to mild undernutrition, using the sexually mature male sheep as a model. Testis regression leads to reductions in daily sperm production and in the quality of ejaculated spermatozoa (poorer movement, DNA damage). There is also a reduction in spermatogenic efficiency that appears to be caused, at least partially, by increases in germ cell apoptosis. Sertoli cell num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 77 publications
0
10
0
1
Order By: Relevance
“…BCL2 is also highly expressed in Sertoli cells of sexually mature animals, which may be essential to promote survival of these cells since they are essentially quiescent after puberty and cannot be replaced (Aslani et al, 2017). Interestingly, in sexually mature sheep exposed to undernutrition, spermatogenesis reversibly regresses due to the alteration of Sertoli cell function that in turn induces apoptosis in germ cells (Guan and Martin, 2017). Likewise, in the sperm of mice fed a low protein diet, genes involved in apoptosis were found hypomethylated, echoing the hypermethylation we report here in the HM groups (Watkins et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…BCL2 is also highly expressed in Sertoli cells of sexually mature animals, which may be essential to promote survival of these cells since they are essentially quiescent after puberty and cannot be replaced (Aslani et al, 2017). Interestingly, in sexually mature sheep exposed to undernutrition, spermatogenesis reversibly regresses due to the alteration of Sertoli cell function that in turn induces apoptosis in germ cells (Guan and Martin, 2017). Likewise, in the sperm of mice fed a low protein diet, genes involved in apoptosis were found hypomethylated, echoing the hypermethylation we report here in the HM groups (Watkins et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[4] found that the dietary supplementation influences the Sertoli cell function (histological analyses), but it does not affect their number. By contrast, in underfed rams experiencing a reduction in testis mass and spermatogenesis, it seems that differentiation and maturation are reversed in the Sertoli cells, reducing their efficiency as supporters of the germ cells [49]. Because puberty entails the loss of Sertoli cell proliferative ability and the formation of the blood–testis barrier [50,51], it remains therefore to be tested whether in fallow deer yearlings, the high nutritional intake may have influenced the Sertoli cell number or its maturational development during puberty.…”
Section: Discussionmentioning
confidence: 99%
“…The variation among quail strains in age‐related declines in sperm kinematics and other aspects of reproductive performance might be explained in several ways: (a) as a side‐effect of intensive selection of quail for growth rate, with subsequent effects on metabolic endocrine systems (Ottinger, ), many of which are known to affect testis function in mammals (Guan & Martin, ); (b) variation in the age at which quail present with testicular pathology, such as Sertoli cell tumours, diseases that would decrease sperm production (Gorham & Ottinger, ); (c) decline with age in the activity of testosterone dependent aromatase and arginine vasotocin (Panzica, Aste, Viglietti‐panzica, & Ottinger, ), leading to declines in intra‐testicular and circulating concentrations of testosterone, a critical factor in spermatogenesis, seminiferous tubule integrity, the production of seminiferous fluid; (d) variation in the seasonality of reproductive activity (Thurston & Korn, ); (e) variation in the secretion of Ca +2 and glutamate by the accessory reproductive glands (Froman & Feltmann, ); (f) variation in morphology and function of sperm mitochondria, factors known to depend on genetics in the chicken (Froman & Kirby, ); and (g) variation in the size and function of the cloacal glands that produce the foam that is important for sperm motility in quail (Farooq et al, ).…”
Section: Discussionmentioning
confidence: 99%